Why do Russian Firms Use Fixed-Term and Agency Work Contracts? - Smirnykh, Larisa (OECD Economics Department Working Papers, 2013)
This study looks into the use of fixed term contracts and agency work in Russia during and shortly after the crisis 2009-10 with the help of an enterprise survey. The results of variance analysis show that the use of fixed-term or agency work contracts is not uniform across sectors, size and skill requirements. Probit analysis reveals that the use of fixed term contracts also in-creases the likelihood of using agency work, but not the other way around. The increase of tem-porary and agency work contracts increases the turnover on the labour market and contributes to an increase in dualisation, but may also help to prevent a larger increase in unemployment during crisis periods